The possible anti-tumor actions and mechanisms of active metabolites from Cortex Fraxini - Cai, Bin; Cai, Ting; Feng, Zeyu; Zhu, Huanhuan (Frontiers in Pharmacology, 2024)
Cortex Fraxini is a traditional Chinese herb that is widely available, inexpensive, and has low toxicity. Modern pharmacological studies have demonstrated that the active metabolites in Cortex Fraxini, including esculin, esculetin, and fraxetin, exert antitumor activities by regulating genes and proteins involved in cancer cell proliferation, apoptosis, invasion, and migration. Additionally, these metabolites play a pivotal role in the regulation of several tumor-associated signaling pathways, including the PI3K/Akt, MAPK/ERK, JAK/STAT3, and Wnt/β-catenin pathways. Due to their proapoptotic and anti-proliferative properties in vitro and in vivo, Cortex Fraxini and its active metabolites may be considered as potential candidates for the treatment of tumor.The aim of this review is to highlight the anti-tumor biological activities and underlying mechanisms of action of the active metabolites of Cortex Fraxini, with a view to providing a reference for their further development and application in the treatment of tumors.